ANALISIS PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Saputra, Akhmad Julian; Setiawati, Dewi; Pratiwi, Lusiana (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2024)
Abstract, This study aims to examine: (1) work motivation on job satisfaction (2) work motivation on performance (3) job satisfaction on employee performance. This research is quantitative using primary data, the population in this study are all employees of PT Krisna Indonesia Tbk Banjarmasin Branch. The sampling technique in this study used saturated sampling, which amounted to 30 respondents. The data collection method is carried out through a questionnaire distributed to employees of PT Krisna Tbk in 2023. The data obtained is then processed using the SPSS tool version 20. This analysis includes reliability test, validity test, statistical test through normality test, T test test and determinant coefficient (R2), and path analysis test. The results of research on work motivation affect job satisfaction, work motivation affects employee performance. Job satisfaction affects employee performance.